Subjective and physiological responses to the 35% carbon dioxide challenge in healthy and non-clinical control populations: a meta-analysis and systematic review. Issue 2 (4th March 2019) - Liu, Jenny J. W.; Ein, Natalie; Gervasio, Julia; Vickers, Kristin
ABSTRACT: Background/Rationale: The carbon dioxide (CO2 ) challenge has been reliably used in laboratory settings as a panicogen in clinical populations. However, the magnitude of these effects on healthy and non-clinical control populations are not clear. The aim of this meta-analysis and systematic review is to provide quantitative estimates of those effects. Specifically, the current paper will evaluate the relative efficacy of the CO2 challenge in eliciting both subjective and physiological arousal in healthy and non-clinical control populations. Method: A total of 16 articles with 35 independent samples were included in the meta-analysis, while 37 studies with 74 independent samples were included in the systematic review. Results: Both the meta-analysis and systematic review found the CO2 challenge to elicit an increase in subjective distress via self-reported anxiety and fear. Physiological responses via blood pressure and heart rate were heterogeneous in studies sampled, with no significant changes observed across studies. Moderator analyses revealed the variations in findings may be attributed to participant screening and invasive sampling. Discussion: Findings highlight the CO2 challenge as a useful tool in the provocation of subjective distress. Implications for both the use of the CO2 challenge and its anticipated effects in healthy and non-clinical control populations are discussed.